Goya and the Mystery of Reading - Martín-Estudillo, Luis (Book collections on Project MUSE., 2023)
"Goya and the Mystery of Reading studies the way Goya's work heralds the emergence of a new kind of viewer, one who he assumes can and does read, and whose comportment as a skilled interpreter of signs alters the sense of his art, multiplying its potential for meaning. While the reading evolution resulted from and contributed to the momentous social transformations of the late eighteenth and early nineteenth centuries, Goya and the Mystery of Reading explains how this transition can be tracked in the work of Goya, an artist who aimed not to copy the world around him, but to read it"--